From Clampdown to Limited Empowerment: Hard and Soft Law in the Calibration and Regulation of Religious Conduct in Singapore - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2009)
The focus of Singapore's response to terrorism post 9/11 has been to reach out to the “moderate, mainstream” Muslims as a bulwark against societal implosion. This article examines the broad-based endeavor toward “religious moderation.” While coercive draconian legislation remain the mainstay against extremists and radicals, the mobilization of soft law, aspirational norms, and values are consciously woven into the state's endeavors to enhance society's resilience and cohesion. They also seek to regulate religious conduct at a time when the state wishes to entrench secularism as a cornerstone of the governance of a multi-racial, multireligious society. Rights and regulation are not antithetical to each other; they are integral to the entire process of managing sociopolitical risks that presents a real danger of an incivility spiral in which distrust, fear, and suspicion conspire toward societal breakdown.